Fleas - P.G. Koehler (EDIS)
This document provides an overview of fleas, including their biology, life cycle, and the health issues they cause. Fleas are small, blood-sucking insects that can infest pets and homes, causing itching and irritation. The document details the flea’s life stages, from eggs to adults, and emphasizes the importance of treating both pets and their environments to control infestations. It also discusses various treatment methods, including on-animal treatments and premise treatments, to effectively manage and prevent flea problems. Date first printed July 1993.